Bacteremia due to Helicobacter cinaedi in Two Patients with Human Immunodeficinecy Virus Infection. (1st June 1992) - Simor, Andrew E; Brunton, James L
Abstract : Helicobacter cinaedi (formerly Campylobacter cinaedi ) has been associated with enteric disease in homosexual men. The authors report two cases of H cinaedi bacteremia occurring in patients with human immunodeficiency virus (HIV) infection. These cases illustrate that H cinaedi may act as an opportunistic pathogen in patients with HN infection or the acquired immune deficiency syndrome.